Sex-specific association between maternal childhood adversities and offspring’s weight gain in a Brazilian cohort - Vinicius Oliveira Santana; Aline Camargo Ramos; Hugo Cogo-Moreira; Célia Maria Araújo; Barbara Shibuya Alves; Lucas Ribeiro; Aline Lodi; Ana Carolina Coelho Milani; Ivaldo Silva; Cristiane S. Duarte; Jonathan Posner; Andrea Parolin Jackowski (Scientific Reports)
Abstract Maternal adverse childhood experiences (ACEs) are linked to negative health and developmental outcomes in offspring. However, whether maternal ACEs influence infant weight gain in the first months of life, and if this effect differs by infant sex, remains unclear. This study included 352 full-term newborns from low-risk pregnancies and their mothers in low-income settings in Brazil. Anthropometric data (weight, length, head circumference) and other information (feeding type, offspring sex, family income) were collected at delivery (W0), discharge (W1), and up to 8 weeks postpartum (W2). ACEs were assessed using the CDC-Kaiser Questionnaire, and weight gain was calculated as the difference between W2 and W1, divided by the number of days between measurements. The association between maternal ACEs and offspring weight gain was positive only in male offspring (unstandardized coefficient (male) = 1.82, SE = 0.438, p < 0.001); for each 1-point increase in the ACEs score (e.g., from 0 to 1), weight gain increased by 1.8 g/day. These findings indicate that maternal ACEs are associated with increased weight gain in male infants during the first two months of life, potentially increasing the risk of future obesity. Further research is required to investigate the underlying biological mechanisms and their neurodevelopmental implications.